The effects of foot massage on restless leg syndrome in hemodialysis patients: A systematic review - Kusnendar, Kusnendar; Awaludin, Sidik (Holistik Jurnal Kesehatan, 2024)
Background: Restless leg syndrome (RLS) is a neurological disorder that causes an irresistible desire to move the legs. RLS is a problem that is often encountered in hemodialysis (HD) patients and can affect the patient's quality of life. Purpose: To compare the effectiveness of massage therapy and aromatherapy on symptoms of restless leg syndrome and sleep quality in hemodialysis patients. Method: Systematic review study design that refers to the Preferred Reporting Items for Literature Review and Meta-Analyses (PRISMA). The literature used was published from 2013-2023 through databases including, ProQuest, Science Direct, Cochrane, Ebsco Host, SAGE Journal, Taylor & Francis, and Scopus with the keywords "Restless Leg Syndrome", "Leg Massage", and "Dialysis". Results: This study recorded significant massage interventions in hemodialysis patients in seven articles with varying massage methods, including stretching, reflexology, and Swedish massage. Another method also adds aromatherapy massage using essential oils. Muscle massage can increase relaxation and blood circulation in the legs, as well as improve the patient's sleep quality. Adding sensory nerve stimulation using aromatherapy will increase the patient's relaxation speed. Apart from massage therapy using hands, vibrators can also be used and have been proven to be effective in reducing restless leg syndrome. However, currently the use of vibrators is not yet widespread. Conclusion: Massage therapy is effective in reducing restless legs syndrome and improving the quality of life of hemodialysis patients. When carrying out massage therapy, several types of lubricants can be used to increase the effectiveness of massage therapy, such as lavender, olive oil, glycerine and citrus.   Keywords: Dialysis; Foot massage; Restless Legs Syndrome (RLS).   Pendahuluan: Restless leg syndrome (RLS) merupakan gangguan neurologis yang menyebabkan keinginan yang tidak dapat ditahan untuk menggerakkan kaki. RLS menjadi salah satu permasalahan yang sering ditemui di kalangan pasien hemodialisis (HD) dan dapat memengaruhi kualitas hidup pasien. Tujuan: Untuk membandingkan efektifitas terapi pijat dan aromaterapi terhadap gejala sindrom kaki gelisah serta kualitas tidur pada pasien hemodialisis. Metode: Desain studi sistematik review yang merujuk pada Preferred Reporting Items for Literature Review and Meta-Analyses (PRISMA). Literatur yang digunakan merupakan terbitan dari tahun 2013-2023 didapat melalui database antara lain, ProQuest, Science Direct, Cochrane, Ebsco Host, Jurnal SAGE, Taylor & Francis, serta Scopus dengan kata kunci "Restless Leg Syndrome", "Leg Massage", dan "Dialysis". Hasil: Penelitian ini mencatat intervensi pijat yang signifikan terhadap pasien hemodialisis dalam tujuh artikel dengan metode pijat bervariasi, termasuk peregangan, refleksologi, dan pijat Swedia. Metode lain juga menambahkan pijatan dengan aromaterapi menggunakan minyak esensial. Pijatan otot dapat meningkatkan relaksasi, dan peredaran darah di kaki, serta memperbaiki kualitas tidur pasien. Penambahan stimulasi saraf sensorik menggunakan aromaterapi akan meningkatkan kecepatan relaksasi pasien. Selain terapi pijat menggunakan tangan, vibrator juga dapat digunakan dan terbukti efektif mengurangi restless leg syndrome. Akan tetapi, saat ini penggunaan vibrator belum luas. Simpulan: Terapi pijat efektif dalam mengurangi restless leg syndrome dan meningkatkan kualitas hidup pasien hemodialisa. Dalam melakukan terapi pijat, beberapa jenis pelumas dapat digunakan untuk meningkatkan efektifitas terapi pijat seperti, lavender, minyak zaitun, gliserin, dan citrus.   Kata Kunci: Dialisis; Pijat Kaki; Sindrom Kaki Gelisah.